Mycobiota on common wheat ( Triticum aestivum) and spelt (Triticum aestivum ssp. spelta) grains from the region of Vojvodina in 2015 - Krulj Jelena A. (Food and Feed Research, 2016)
The incidence of mycobiota on common wheat (Triticum aestivum) and spelt (Triticum aestivum ssp. spelta) samples, collected during the harvest in 2015, was investigated. The obtained results showed that more genera of mycobiota were isolated from the common wheat grains than from the spelt grains. The most frequently isolated species from common wheat grains belonged to genus Alternaria (41.7%), followed by Fusarium (15.2%), while the incidence of this mycobiota on the spelt grains were 32.4% and 10.4%, respectively. Aspergillus flavus was identified in 40.0% wheat samples, with the incidence of 2.0%. Additionally, this study was undertaken in respect of the occurrence and toxigenic potential of A. flavus isolates from these small grain cereals. A simple screening method was applied to determine toxigenic profiles (aflatoxins production) of A. flavus isolates from common wheat. The results revealed the importance of precise investigation of mycobiota distribution on common wheat and spelt grains, and especially the investigation of toxigenic potential of A. flavus.